The Influence of Social Media Promotion, Product Quality, and Product Price on Consumer Purchase Decisions at Daviena Skincare Kediri - Puspita, Farsa; Kurniawan, Rony (Universitas Nusantara PGRI Kediri, 2025)
Research aim : To analyze the effects of social media promotion, product quality, and pricing on Daviena Skincare's consumer decisions in Kediri. Design/Methode/Approach : Quantitative study using survey data collected from a business owner, a loyal consumer, and a new consumer, analyzed using statistical methods. Research Finding : Social media promotion strongly influences purchasing decisions, while product quality builds loyalty and competitive pricing attracts new customers. Theoretical contribution/Originality : Integrates social media, quality, and pricing as interrelated factors for consumer behavior in local skincare brands, addressing gaps in prior studies. Practitionel/Policy implication : Local skincare brands should leverage social media, ensure product quality, and adopt balanced pricing to compete effectively. Research limitation : Focused on one local brand in Kediri, limiting generalizability, future research should expand to other regions and use quantitative methods.